On the ignition of H11B fusion fuel - Ghorbanpour, Esmat; Belloni, Fabio (Frontiers in Physics, 2024)
We have revisited recent results on the ideal ignition of H 11 B fuel, in the light of the latest available reactivity, an alternative self-consistent calculation of the electron temperature, an increased extent of the suprathermal effects and the impact of plasma density. At high density, we find that the ideal ignition temperature is appreciably relaxed (e.g. 𝑇 𝑖 ≃ 150 keV for 𝑛 𝑖 ∼ 10 26 cm -3 and an optimal 11 B/H concentration 𝜀 = 0.15) and burn becomes substantial. We have then investigated central hotspot ignition in both isobaric and isochoric inertial confinement configurations. Although implosiondriven ignition appears to be unfeasible, the isochoric self-heating conditions foster favourable preliminary conclusions on the utilization of proton fast ignition. In the isochoric case, we find a broad minimum in the ignition energy at 𝜌𝑅 ≃ 8.5 g/cm 2 and 220 ≲ 𝑇 𝑖 ≲ 340 keV (80 ≲ 𝑇 𝑒 ≲ 95 keV), for 𝜀 = 0.15.